A comparison of the histopathologic pattern of the left atrium in canine dilated cardiomyopathy and chronic mitral valve disease - Janus, Izabela (BMC Vet Res, 2016)
BACKGROUND: Dilated cardiomyopathy (DCM) and chronic mitral valve disease (CMVD) in dogs are associated with heart chamber enlargement, also of the left atrium. DCM is often accompanied by rhythm disturbances (mainly atrial fibrillation or ventricular arrhythmias). In CMVD, arrhythmias are observed less frequently. It is still unclear whether left atrial enlargement in these diseases results from volume overload or if it is also connected with other factors (e.g. rhythm disturbances). This study was conducted on the left atrial myocardial specimens from 31 dogs, including those from 16 dogs with clinically diagnosed DCM and 15 dogs with CMVD. After fixation and staining (using haematoxylin-eosin and Masson-Goldner trichrome stain), the specimens underwent evaluation. Parenchymal changes (fibrosis, fatty infiltration, and vessel narrowing), degenerative changes (loss of striation, changes in cardiomyocyte structure, and abnormal cell nuclei) and the presence of inflammatory infiltrates were assessed. RESULTS: More interstitial fibrosis (median 4 vs. 2.5 grid fields; p < 0.05) and less perivascular fibrosis (median score 1 vs. 2; p < 0.05) was observed in the DCM group compared to the CMVD group. Moreover, less distinct vessel narrowing was observed in the DCM group than in the CMVD group (median lumen area ratio 0.3 vs. 0.26 respectively; p < 0.05). Dogs with DCM showed more strongly defined degenerative changes than the CMVD dogs (median nuclei enlargement score 3 vs. 1, median loss of striation score 3 vs. 2 and median structural alterations score 3 vs. 2, respectively; p < 0.05). CONCLUSION: The obtained results indicate a different nature of changes occurring in the left atrial myocardium of dogs with DCM compared to dogs with mitral valve disease, including differences in vessel narrowing, cardiomyocyte degeneration and in the distribution of connective tissue.